Anti-hyperglycemic Effect of Paeonia Lactiflora Pall Roots Extract on normal rat model - misanjas, Nisreen Abdul karirm Abdul Aali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In the present study antihyperglycemic activity was evaluated in ethanolic root Extract of Paeonia lactiflora in noroglycemic Rats. Extract at Dose 250mg/Kg had Effect non significant different (p<0.05) to glimepiride at Dose 8mg/Kg, 90 minutes after Glucose Load Peonia Lactiflora Pall a significant blood sugar lowering Effect The antihyperglycemic activity of of Peonia Lactiflora Pall was designed in normoglycemic Rats .preparatory qualitative chemical screening Indicate the presence of "saponins,tannins, ,triterpens,flavonoids, and glycosides in ethanolic Root Plant". LD50 doses ethanolic root Plant was studied Results this study showed no mortality rate from ascending doses until 2gm/kg B.Wt. was occurred